Interlink between Obesity Hypoventilation Syndrome and Obstructive Sleep Apnea. Do we need to screen patients for OHS in obese OSA patients? - Dhakal, S.S.; Maskey, R.; Bhattarai, M. (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Introduction: Around 90% of patients with OHS have coexistent obstructive sleep apnea (OSA) defined by an apnea–hypopnea index (AHI) >5 events/h, with nearly 70% having severe OSA (AHI > 30 events/h). Prevalence of OHS is between 8% and 20% in obese patients referred to sleep centers for evaluation of SDB. As prevalence of OHS in OSA patients data from Nepal is not available we planned to carry out the study and to address gaps in diagnosis and management. Methodology: This is a cross sectional observational study done in OM hospital and research centre from 2018 January to 2019 June. Awake daytime Arterial blood gas ( ABG) was obtained and patients having PaCO2 more than 45 mmHg were diagnosed as obesity hypoventilation syndrome in a recently diagnosed patients with OSA. Results: 32 patients diagnosed to have OSA and whose BMI is more than 30 were included in the study. Among 32 patients 26 (81.25%) were male and 6 (18.75) were female. Among all patients who underwent level A polysomnography 3 (12.5%) had mild OSA,4(16.66%) had moderate and 17 (53.12%) had severe OSA. 8 (25%) patients had normal diagnostic polysomnography. Among these patients 3(12.5%) who had mild OSA has BMI between 30-35,16 (66.66%) patients who had BMI between 30-35, 2 had mild 3 had moderate and 11 had severe OSA. Patients with BMI more than 40,5 (28.3%) had OSA among which 21 had moderate and 4 had severe OSA. Conclusions: As OHS is often misdiagnosed even in patients with severe obesity, we strongly recommended screening in obese patients with OSA for OHS as early recognition and effective treatment are important in improving morbidity and mortality in this group of patients.